ANALISIS POTENSI PENYEBAB KECELAKAAN KERJA DI PABRIK KELAPA SAWIT MENGGUNAKAN METODE HAZARD IDENTIFICATION AND RISK ASSESSMENT (HIRA) DAN JOB SAFETY ANALYSIS (JSA) - Putra Sandika, Dwi; Dyah Prabaswari, Atyanti; Iqbal Rofif, Muhammad; Agung Jatmiko, Hapsoro; Padhil, Ahmad (Universitas Putera Batam, 2025)
CIN operates in the cultivation and processing of Crude Palm Oil (CPO) at the Kedukul Palm Oil Mill (PKS), which includes six main processing stations: Rame Loading, Boiling (Sterilizer), Bantingan (Tresher), Pressing, Palm Kernel, and Clarification. This study aims to identify potential hazards that may lead to occupational accidents in the CPO processing area, assess the associated risk levels, and propose mitigation strategies to reduce critical risks. The research employs Hazard Identification and Risk Assessment (HIRA) alongside Job Safety Analysis (JSA) to systematically evaluate work activities across stations. Results indicate that the Boiling Station carries the highest total risk score of 45, followed by the Pressing Station (39), Rame Loading (37), Bantingan (31), Clarification (23), and Palm Kernel Station (20), which has the lowest risk. Recommendations focus on hierarchical risk controls, including: (1) Engineering controls such as installation of warning signage and hazard symbols; (2) PPE management by ensuring the consistent use of safety glasses, helmets, gloves, earplugs, and safety footwear; (3) Administrative controls through scheduled Occupational Safety and Health (OSH) training and dissemination of safety awareness among workers; (4) Substitution controls by regularly replacing hazardous components such as slings and truck hooks in the Boiling Station; and (5) Elimination strategies by deactivating machinery or sources with high accident potential. The integration of these measures is expected to significantly improve occupational safety performance in palm oil processing operations.